Case Report: Acute Spinal Cord Myelopathy in Patients With COVID-19 - Khedr, Eman M.; Karim, Ahmed A.; Soliman, Radwa K. (Frontiers in Neurology, 2020)
COVID-19 is typically associated with fever and severe respiratory symptoms including headache, dizziness, dry cough and dyspnea. However, in COVID 19, both central and peripheral nervous systems can be affected as well. Till today, the incidence rate of spinal cord involvement in COVID‑19 is not known and the pathogenesis is still not fully understood. We report here two female cases with spinal cord involvement out of 439 cases (0.5%) with COVID-19 admitted to the Assiut University Hospitals in Egypt. The first case is a 60 years old female patient with acute onset of flaccid paraplegia, after 10 days of flu like symptoms MRI revealed transverse myelitis. The second case is a young 21-year-old female patient showing symptoms of acute quadriplegia, fever, headache and insomnia. MRI revealed cervicodorsal myelopathy secondary to anterior spinal artery occlusion. Both observations followed acute COVID-19 pneumonia.